Dimas: Gay yang Pernah Nikah Secara Heteroseksual (Sebuah Life History) - Nugroho, Adi (Faculty of Psychology, Universitas Surabaya, 2007)
This is a life history (LH) of Dimas, a gay who had been married heterosexually. LH is aimed to understand the individual through his appreciation on experiences he feels happening in his life, as well stressing his relationship with the author. LH is also used to understand how people live and work in a colonial context (oppression), oppression against homosexuality as a minority discourse. Data in this article were obtained from Dimas’ narrations, which the author collected through in-depth interviews. Other data were obtained from Dimas’ self-portrait, and other relevant researches. Results reveal Dimas’ understanding of his sexual orientation, as well as the understanding of experiences he seems to experience. Secondly the interaction of Dimas and his culture in a social construction context and the development of the homosexuality issue in Indonesia. Karya ini merupakan life history (LH) Dimas, gay yang pernah nikah secara heteroseksual. LH bertujuan memahami individu melalui pemaknaan dirinya atas peristiwa-peristiwa yang dimaknainya telah terjadi di kehidupannya, di samping juga menggarisbawahi hubungan individu dengan peneliti. LH digunakan untuk mengerti bagaimana manusia hidup dan bekerja dalam konteks kolonial (penindasan), dalam hal ini penindasan atas homoseksualitas sebagai wacana minoritas. Data yang digunakan di sini, yang utama adalah narasi Dimas yang peneliti peroleh melalui in-depth interview. Data lain berupa catatan harian dan potret diri Dimas, serta penelitian lain yang terkait. Hasil penelitian ini, yang pertama adalah pemaknaan Dimas atas orientasi seksualnya, termasuk pemaknaan atas rangkaian peristiwa yang menurutnya telah terjadi. Kedua adalah interaksi Dimas dengan budayanya dalam konteks konstruksi sosial dan perkembangan isu homoseksualitas di Indonesia.